Belajar Dari Kelompok Bu Manik : Partisipasi Masyarakat Dalam Program CSR PT. Pertamina Fuel Terminal Bandung Group - Haerul Jamal; Tia Fitriani; Erick Abriandi (UIN Siber Syekh Nurjati Cirebon, 2021)
National development is not only the responsibility of the State, the role and involvement of all aspects including the corporation and the community are important in national development efforts. One of the roles taken by the corporation in national development efforts is through the Corporate Social Responsibility program or CSR. In practice, the activity of Corporate Social Responsibility is one of the forms of community empowerment which carried out by the company. As a form of empowerment, CSR is not only a mere philanthrophy or caricative activity, however it must uphold the elements of the community's based development, namely participation so that the programs that are established can make the community energize the problem continuously. This study tries to explore how public participation in the CSR program of magot cultivation and organic waste (BU MANIK) which carried out by PT Pertamina Fuel Terminal Bandung Group in RW 02 Cipamokolan Sub-District, Rancasari Subdistrict, Bandung, West Java, which is Ring 1 of Pertamina Fuel Terminal Bandung Group. This study uses descriptive qualitative research methods, the results of the study indicate that this BU MANIK Program has provided more space to the community to participate in the stage of planning, implementation, evaluation, and utilization. The existence of community participation in the BU MANIK program in every stage establishes this program runs continuously and a sustainable way that has been in 2019 until now.